Cicero's law : rethinking Roman law of the late Republic - Plessis, Paul J. du (Edinburgh University Press, 2016)
"In his 1995 book 'The spirit of Roman law, ' Alan Watson included a chapter ... titled 'Cicero the outsider.' Watson's argument, following the then dominant Romanist view, was that Cicero's outlook was significantly different from that of the Roman jurists. While Watson's cautious observation has merit in the context of his argument, its subtext is more problematic. It is the purpose of this volume to critique the pervasive view in Roman-law literature that minimises the significance of Cicero in the narrative of Roman law of the late Republic. This reappraisal of the significance of Cicero reflects current thinking in Roman law and forms part of a larger and more complex debate concerning the nature of law and of the legal profession in the last century of the Roman Republic."-- Back cover.
Keywords: Cicero, Marcus Tullius.; Cicero, Marcus Tullius -- v106-v43; Cicéron, -- (0106-0043 av. J.-C.); Roman law.; Rome -- Politics and government -- 265-30 B.C.; Rome -- History -- Republic, 265-30 B.C.; LAW -- Essays.; LAW -- General Practice.; LAW -- Jurisprudence.; LAW -- Paralegals & Paralegalism.; LAW -- Practical Guides.; LAW -- Reference.; Politics and government.; Rome (Empire); Römisches Recht; Rome -- Politique et gouvernement -- 264-30 av. J.-C.; Classical history / classical civilisation; 265-30 B.C.; Electronic books.; History.